Men and Women Who Made America Great - Basini, Eugene C (River Forest, Illinois Laidlaw Brothers Publishers, 1979)
Biographical sketches of men and women instrumental in various aspects of American history from early exploration to music and dance.
Include Maps, Illustrations, Glossary and Index.
It is a biography.
Keywords: United States -- North America -- United States -- Biography -- Juvenile literature -- North America -- Biography -- Juvenile literature -- United States -- Biography